Development of Islamic Digital Library - Abdul Shukor, Nur Liyana Shafiqah; Norfaiza Fuad,; Tukiran, Zarina (Evolution in Electrical and Electronic Engineering, 2023)
This study addresses several challenges related to the storage and management of digital Islamic manuscripts. Firstly, the lack of appropriate technology for storing these manuscripts poses a significant hurdle. Additionally, there is a need for a platform that enables efficient management of manuscript collections and assists administrators in handling them effectively. To tackle these issues, the study proposes the development of a specialized database using MySQL, which is well-suited for document storage. Furthermore, Python is selected as the backend programming language for server-side development. The goal is to create a user-friendly platform that allows administrators to easily add or delete books from the collection. Finally, the study aims to evaluate the software testing conducted in the software environment to ensure the complete system behaves as intended. The anticipated outcome of this research is the development of a comprehensive platform that grants full administrative access and effectively addresses the challenges associated with storing and managing digital Islamic manuscripts.